Overall fuzzy logic control strategy of direct driven PMSG wind turbine connected to grid - Mhamed Fannakh; Mohamed Larbi Elhafyani; Smail Zouggar; Hassan Zahboune (Institute of Advanced Engineering and Science, 2021)
The fuzzy logic strategies reported in the literature about the control of direct drive permanent magnet synchronous generator (PMSG) connected to grid are limited in terms of inclusiveness and efficiency. So an overall control based on fuzzy logic and anti-windup compensation is proposed in this paper. Aiming at the inadequate of hill climb search (HCS) MPPT with fixed step size, the fuzzy logic is introduced in the stage of